An analysis of factors affecting bidders’ decision of mergers and acquisitions: Empirical results from the UK - Cheng, Xumin (2010)
The subject of mergers and acquisitions is popular since the development of globalisation. This piece of work studies the factors which would affect the bidders’ decisions of M&As in 2009. In the UK market, number of M&A deals decreased sharply from 2008 to 2009 because of economy recession. It is interesting to find out if the influence factors would change in this special time. The study examines variables of firm characteristics and industrial factors. By running logit regression models, the results shows variables of industrial factors are not significant. While there are different significant variables of firm characteristics in the entire sample size and subsamples. In addition, this research has different findings compared to the previous studies. For example, the debt to assets ratio was a significant variable in the early M&A activities. However, in this research it is not significant in all regression models. It can be assumed that firms are more cautious in making M&A strategies in 2009. To reduce risk, even firms with good liquidity do not want to increase debts to acquire other firms.